Blunted cardiac autonomic dynamics to active standing test in postmenopausal women - Scatà, Costanza; Ferreira, Felipe C.; Padilha, Michelle C. S. V.; Carandina, Angelica; Asnaghi, Riccardo; Bellocchi, Chiara; Tobaldini, Eleonora; Montano, Nicola; Soares, Pedro Paulo da S.; Rodrigues, Gabriel D. (Frontiers in Cardiovascular Medicine, 2024)
Introduction Although both aging and menopause influence cardiovascular autonomic control, the effect of menopause per se remains unclear. The current study was undertaken to test the hypothesis that post-menopausal women (PMW) have a blunted cardiovascular autonomic adjustment to active standing compared to pre-menopausal women. Thus, we compared the heart rate variability (HRV) indexes from supine (SUP) to orthostatic (ORT) positions among young women (YW), young men (YM), older men (OM), and PMW. Methods The participants rested for 10 min in SUP and then stood up and remained for 5 min in ORT. ECG was continuously recorded, and R-R time series of about 300 beats were analyzed using linear (spectral analysis) and non-linear (symbolic analysis) methods. The variation from SUP to ORT was calculated (Δ = ORT-SUP) for each HRV index. Results In SUP, no difference was found for any HRV index among groups. However, Δ0V% and ΔLFn (cardiac sympathetic modulation) were reduced in PWM compared to all groups (OM, YW, and YM), while Δ2UV% and ΔHFn (cardiac vagal modulation) were reduced in PMW than the younger group (YW and YM). No differences were found among the male groups (OM and YM). Discussion In light of our results, the cardiac autonomic dynamic response to orthostatic stress is blunted in post-menopausal women compared to younger women and older men, a finding that might be influenced not only by aging.